Efisiensi Alokasi Aset untuk Meningkatkan Kinerja Keuangan Perusahaan pada Industri Manufaktur Indonesia - Amo Sugiharto; Heriyanti Heriyanti; Yulhendri Yulhendri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the efficiency of assets in the Indonesian manufacturing industry sector in obtaining sales, particularly in the post-pandemic era. Despite the growing enthusiasm of both domestic and foreign investors in the sector, there has been an increase in layoffs (PHK), which poses a paradoxical situation. On one hand, investors are showing interest in the manufacturing industry, while on the other hand, there is an unfortunate rise in the number of employees being laid off. This contradiction sparks interest in analyzing the efficiency with which manufacturing companies utilize their assets to generate sales. The research uses secondary data from the Indonesia Stock Exchange (IDX) from 2021 to 2023, focusing on the manufacturing industry. The analysis employs financial ratio analysis, specifically the Total Asset Turnover ratio, to assess asset utilization. The findings show that the Total Asset Turnover ratio is 0.94X, which is below the industry standard of 1.1X (0.94 < 1.1). This indicates that the asset efficiency in obtaining sales is relatively low. The results suggest that manufacturing companies should evaluate and revise their policies to ensure that their assets are utilized more effectively. By designing accurate and targeted sales strategies, companies can improve their asset turnover and optimize their operations. This research highlights the importance of evaluating asset efficiency in the context of sales generation, especially in a sector experiencing contrasting dynamics between investor enthusiasm and rising layoffs. It emphasizes that strategic planning and policy adjustments are crucial for manufacturing companies to achieve better outcomes in terms of asset utilization and sales performance.